Jurnal Pencegahan dan Penanganan Kekerasan Seksual menggunakan Natural Languange Process dan Data Science - Alissyah Putri; Dani Azka Faz; Anshari Rusmeniar R.A; Yuni nur fari'ah; Falah Arfani; Faisal Dharma Adhinata (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Violence against women is something that is often heard and discussed in society. Women are often victims of discrimination, harassment and violence. Sexual harassment and violence in Indonesia is certainly not only experienced by adult women, but can also be experienced by children and adult men. Although in many cases it is more experienced by women. Of all respondents who were victims of sexual violence, almost all preferred or decided not to report the sexual violence and harassment they experienced. The cause is a psychological problem because of what happened to him, which makes him confused, embarrassed, afraid and even feels self-blame for what he experienced. This is the basis for the author to build a Chatbot and Recommendation System as a form of care and also a solution for victims of sexual violence by presenting a website "preventing and handling sexual violence". Chatbots serve as a forum for information related to sexual violence such as definitions, boundaries of sexual violence categories, complaint reporting services, and as a legal umbrella that can be used to protect themselves and criminals who commit sexual violence. The data source was obtained from the Law on the Elimination of Sexual Violence. By having easily accessible legal information and official data sources, the author hopes that this can help victims to have the courage to take steps to report the acts of violence they have experienced. The recommender system provides recommendation results in the form of information on legal services and psychological consultations. Not a few victims of sexual violence certainly experience psychological problems such as feelings of confusion, shame towards other people, fear of the perpetrator, not to mention feelings of guilt that seem to blame themselves for what they have experienced. Information on psychological services is available for victims who need psychological recovery.